2010
DOI: 10.1007/s00299-010-0859-z
|View full text |Cite
|
Sign up to set email alerts
|

Hormonally regulated overexpression of Arabidopsis WUS and conifer LEC1 (CHAP3A) in transgenic white spruce: implications for somatic embryo development and somatic seedling growth

Abstract: Adult conifers are still recalcitrant in clonal propagation despite significant advances in forest tree biotechnology. Plant regeneration through somatic embryogenesis from explants older than mature zygotic embryos is either difficult or impossible to achieve. To investigate if ectopic expression of transcription factors involved in the induction of the embryogenic process would induce somatic embryogenesis in Picea glauca (white spruce) somatic plants, we used the LEAFY-COTYLEDON1 homolog cloned from Picea m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
1
31
1
Order By: Relevance
“…In this respect, in contrast to the recent data on the diverse effects caused by overexpression of LEC genes documented in Arabidopsis, ectopic expression of LEC1 homolog gene in white spruce did not result in somatic embryo formation (Klimaszewska et al 2010). Similarly, overexpression of LEC2 and BBM genes reported to induce SE in Arabidopsis plants (Stone et al 2001;Boutilier et al 2002) did not promote embryo development in tobacco (Rashid et al 2007;Srinivisan et al 2007).…”
Section: Discussioncontrasting
confidence: 71%
“…In this respect, in contrast to the recent data on the diverse effects caused by overexpression of LEC genes documented in Arabidopsis, ectopic expression of LEC1 homolog gene in white spruce did not result in somatic embryo formation (Klimaszewska et al 2010). Similarly, overexpression of LEC2 and BBM genes reported to induce SE in Arabidopsis plants (Stone et al 2001;Boutilier et al 2002) did not promote embryo development in tobacco (Rashid et al 2007;Srinivisan et al 2007).…”
Section: Discussioncontrasting
confidence: 71%
“…It has previously been shown that the frequency of germinated conifer embryos differentiating embryogenic tissue decreases successively as the age of the germinated embryos increases (Klimaszewska et al 2010;Uddenberg et al 2011). In Norway spruce, the decrease of the embryogenic potential includes both a decrease in the frequency of germinated embryos that initiate embryogenic tissue and a decrease in the number of sites on the embryo explants from which embryogenic tissue protrude (Fig.…”
Section: Overexpression Of Pahap3a Is Not Sufficient To Increase the mentioning
confidence: 91%
“…In angiosperms, it has been shown that overexpression of AtLEC1 in tobacco seedlings is not sufficient to stimulate differentiation of embryogenic tissue (Guo et al 2013). Accordingly, it was not possible to stimulate differentiation of embryogenic tissue in germinated somatic embryos of white spruce (Picea glauca) derived from a transgenic cell line overexpressing a HAP3A gene (Klimaszewska et al 2010). Based on the results from Klimaszewska et al (2010) and observations of the expression levels of a HAP3A gene in Pinus radiata callus lines with varying degrees of embryogenic potential, Garcia-Mendiguren et al (2015) suggested that high expression levels of HAP3A alone is not enough for establishing embryogenic cultures and that additional embryonic regulators are likely required to confer embryogenic potential in conifers (Garcia-Mendiguren et al 2015).…”
Section: Overexpression Of Pahap3a Is Not Sufficient To Increase the mentioning
confidence: 99%
“…Such RP effects are useful for improving the transformation frequency of recalcitrant species in tissue cultures and developing a maker-free screening method (Zuo et al 2002b). Several attempts to induce regeneration using the ectopic expression of WUS have previously been reported in some species other than A. thaliana, such as N. tabacum (Rashid et al 2007), Coffea canephora (ArroyoHerrera et al 2008), Capsicum chinense (SolĂ­s-Ramos et al 2009), white spruce (Klimaszewska et al 2010) and cotton (BouchabkĂ©-Coussa et al 2013). However, it remains to be clarified whether the RP effect of WUS is applicable to more species.…”
Section: Introductionmentioning
confidence: 99%